Application of Information Technology in Zakat Management - Erika Amellia Tamara; Jesi Lipia Malina; Epen Triansah; Jemi Puspita Sari; Andi Harpepen (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
This study aims to describe the application of information technology in the management of zakat. This research is motivated by the distribution of zakat must always be prioritized to alleviate the poor from the poverty line. This research is a systematic literature study approach from various articles discussing zakat, zakat distribution institutions, and information technology. To realize the period of zakat activity, there are six aspects to optimize zakat management. The use of information technology (IT) in managing zakat funds, in addition to facilitating muzaki (people who give zakat) and managers, can also provide accountability and transparency in zakat management.